The Effect of Work Environment and Work Training on Employee Performance of PT. Telkomsel Distributor Center Akar Daya Mandiri - Nindi Anggrika (Junal Ilmu Manajemen, 2018)
The purpose of this study was to determine the effect of the work environment on employee performance, to determine the effect of work training on employee performance and to know the work environment and work training simultaneously on the performance of employees of PT. Telkomsel Independent Root Resource Distributor. The population in this study amounted to 52 employees, and the sample used was a saturated sample, where all members of the population were used as samples, namely all employees of PT. Telkomsel Distributor Center Akar Daya Mandiri totaling 52 permanent employees. Data collection techniques used in this study were documentation, interviews and questionnaires. The analysis technique used in this study is the validity test, reliability test, multiple regression analysis, t test, F test and the coefficient of determination. The result of the research shows that there is a significant and positive influence of work environment variables on employee performance variables on "PT. Telkomsel Akar Daya Mandiri Distributor Center" shown from the results of tcount (4,229)> ttable (2,006) with a significant value of 0,000 <0.05, there are significant and positive influence of job training variables on employee performance variables at PT. Telkomsel Akar Daya Mandiri Distributor Center as indicated by the results of tcount (2.760)> ttable (2.006) with a significant value of 0.008 <0.05, there is the influence of the work environment and job training has a significant effect on employee performance due to the results of Fcount (64,349)> Ftable (3.18) and the significance level of 0,000 below the value of 0.05. R Square is 0.724 or 72.4% which means variations of employee performance with work environment and work training while the remaining 27.6% are other variables not examined by this study, such as motivation, organizational culture and other variables